Targeting of two aspects of metabolism in breast cancer treatment - Gang, Bevan P (Cancer Biol Ther, 2014)
Deregulated metabolism is gaining recognition as a hallmark of cancer cells, and is being explored for therapeutic potential. The Warburg effect is a metabolic phenotype that occurs in 90% of tumors, where glycolysis is favored despite the presence of oxygen. Dichloroacetate (DCA) is a pyruvate dehydrogenase kinase (PDK) inhibitor that can reverse the Warburg effect. PENAO (4-(N-(S-penicillaminylacetyl)amino) phenylarsonous acid) is a novel anti-mitochondrial agent that targets the adenine nucleotide transporter in mitochondria and is currently in clinical trials for solid tumors. We have investigated the targeting of two aspects of metabolism, using DCA to promote mitochondrial activity combined with PENAO to inhibit mitochondrial activity, in breast and other carcinoma cell lines. PENAO was effective at low uM concentrations in luminal (T-47D) and triple negative (MDA-MB-231) breast cancer cells, in normoxia and hypoxia. The cytotoxicity of PENAO was enhanced by DCA by a mechanism involving increased reactive oxygen species in both T-47D and MDA-MB-231 cells, however further investigations found it did not always involve PDK2 inhibition or reduction of the mitochondrial membrane potential, which are the accepted mechanisms for DCA induction of apoptosis. Nevertheless, DCA sensitized all cancer cell lines tested toward apoptosis of PENAO. DCA and PENAO are both currently in clinical trials and targeting cancer metabolism with these drugs may offer options for difficult to treat cancers.